2021
DOI: 10.1371/journal.ppat.1009350
|View full text |Cite|
|
Sign up to set email alerts
|

The purine nucleoside phosphorylase pnp-1 regulates epithelial cell resistance to infection in C. elegans

Abstract: Intestinal epithelial cells are subject to attack by a diverse array of microbes, including intracellular as well as extracellular pathogens. While defense in epithelial cells can be triggered by pattern recognition receptor-mediated detection of microbe-associated molecular patterns, there is much to be learned about how they sense infection via perturbations of host physiology, which often occur during infection. A recently described host defense response in the nematode C. elegans called the Intracellular P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 65 publications
3
41
0
Order By: Relevance
“…Indeed, we found a more pronounced role for zip-1 after viral infection of pnp-1 mutants, which have constitutive expression of IPR genes, including pals-5 (Fig. 6b ) 15 . Of note, our qRT-PCR analysis of pnp-1(jy90) animals showed that elevated pals-5 mRNA levels depend on zip-1 , suggesting that the IPR genes upregulated by zip-1 promote resistance against viral infection (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Indeed, we found a more pronounced role for zip-1 after viral infection of pnp-1 mutants, which have constitutive expression of IPR genes, including pals-5 (Fig. 6b ) 15 . Of note, our qRT-PCR analysis of pnp-1(jy90) animals showed that elevated pals-5 mRNA levels depend on zip-1 , suggesting that the IPR genes upregulated by zip-1 promote resistance against viral infection (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, zip-1 is required for induction of pals-5 p::GFP expression after infection by these two natural intracellular pathogens of the C. elegans intestine. We next tested if zip-1 was required for constitutive expression of pals-5 p::GFP in pnp-1 mutants 15 . Here, we also saw a requirement for zip-1 , as zip-1(jy13); pnp-1(jy90) double mutants had much less pals-5 p::GFP signal compared to pnp-1 single mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations